The immunomodulatory properties of adult skin‐derived precursor Schwann cells: implications for peripheral nerve injury therapy. (8th August 2015) - Stratton, Jo Anne; Shah, Prajay T.; Kumar, Ranjan; Stykel, Morgan G.; Shapira, Yuval; Grochmal, Joey; Guo, Gui Fang; Biernaskie, Jeff; Midha, Rajiv
Abstract: Skin‐derived precursor Schwann cell (SKPSC) therapy has been identified as a potentially beneficial treatment for peripheral nerve injuries. One hypothesised mechanism by which SKPSCs enhance recovery is via the modulation of macrophages. In the present study, we investigated the immunomodulatory properties of adult rat SKPSCs, and demonstrated that these cells expressed a battery of cytokines, including interferon‐γ (IFN‐γ), interleukin (IL)‐1β, and, most abundantly, IL‐6. Whereas macrophages exposed to depleted or fibroblast‐conditioned medium secreted minimal amounts of tumor necrosis factor‐α (TNF‐α), in the presence of SKPSC‐conditioned medium, macrophages secreted > 500 pg/mL TNF‐α. Following the transplantation of SKPSCs into injured rat sciatic nerves, we observed an SKPSC density‐dependent increase in the number of macrophages (Pearson's r = 0.66) and an SKPSC density‐dependent decrease in myelin debris (Pearson's r = –0.68). To determine the effect of IL‐6 in a proinflammatory context, macrophage cultures were primed with either lipopolysaccharide (LPS)/IFN‐γ/IL‐1β or LPS/IFN‐γ/IL‐1β + IL‐6, and this showed a 212% and 301% increase in the number of inducible nitric oxide synthase (iNOS)‐positive proinflammatory macrophages respectively. In contrast to neurons exposed to conditioned medium from unprimed macrophages, neurons treated with conditioned medium from proinflammatory‐primed macrophages showed a 13–26% reduction in neurite outgrowth. Anti‐IL‐6 antibody combined with SKPSC transplant therapy following nerve injury did not alter macrophage numbers or debris clearance, but instead reduced iNOS expression as compared with SKPSC + IgG‐treated rats. SKPSC + anti‐IL‐6 treatment also resulted in a two‐fold increase in gastrocnemius compound muscle action potential amplitudes as compared with SKPSC + IgG treatment. Understanding the mechanisms underlying immunomodulatory aspects of SKPSC therapy and developing approaches to manipulate these responses are important for advancing Schwann cell‐based therapies. Abstract : Transplantation of skin‐derived precursor Schwann Cells (SKPSCs) into injured peripheral nerves has been shown to improve functional recovery. We have shown that an increase in macrophages and enhanced clearance of myelin debris correlates with this recovery. Additionally, we found that IL‐6 is particularly elevated in SKPSCs. Surprisingly, however, IL‐6 appears to be detrimental in this context, since neutralisation of IL‐6 in combination with SKPSC transplant resulted in improved muscle reinnervation after nerve injury.